Urban freight transport measures in São Paulo metropolitan area. - Destro, Maristela Alves Ferreira (2021)
There is a general perception that urban freight vehicles are relevant contributors to worsened livability in urban areas. To address citizens complaints, local authorities interfere usually by regulating truck traffic within their jurisdiction boundaries. The objective of this study is to provide insight in the emergence of UFT management measures in large cities and adjacent areas. It is an exploratory research and, as such, it aims to produce generalizations derived from inductive reasoning. To achieve this objective, we conducted a detailed account of UFT measures in the São Paulo Metropolitan Area from 1960 to 2019. We searched cities document databases and employed Python routines to recognize and filter text information, then compared the emergence of measures with changes in population, GDP, fleet and accidents data. We found that public policies have not been coordinated among cities and that most initiatives are not assessed before implementation.